2022
DOI: 10.1177/11782218221085592
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use in Healthcare Professionals During the COVID-19 Pandemic in Latin America: A Systematic Review and a Call for Reports

Abstract: Background: The COVID-19 pandemic has generated a remarkable change in the behaviour of Healthcare workers (HCWs) around the world. However, there is a lack of evidence on substance use among HCWs in Latin America. Therefore, this study aimed to determine the current frequency of substance use among Latin American among HCWs. Methods: We searched 8 databases (PubMed, Scopus, ScientDirect, Web of Science, Cochrane, Scielo, LILACS and Latindex), 4 public prepublication servers (SocArXiv, medRxiv, bioRxiv and Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A recent nation-wide study in Uruguay revealed that among participants aged 15–65 years, alcohol (52%) and tobacco (33%) were the substances with the highest level of habitual consumption, with women being more likely to increase tobacco use during the COVID-19 pandemic compared with men [ 13 ]. Another study reported that among healthcare workers from Latin America, smoking tobacco increased between 2020 and 2021 [ 14 ]. In contrast, a study in cardiometabolic patients in Latin America revealed that women reported lower tobacco use during the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent nation-wide study in Uruguay revealed that among participants aged 15–65 years, alcohol (52%) and tobacco (33%) were the substances with the highest level of habitual consumption, with women being more likely to increase tobacco use during the COVID-19 pandemic compared with men [ 13 ]. Another study reported that among healthcare workers from Latin America, smoking tobacco increased between 2020 and 2021 [ 14 ]. In contrast, a study in cardiometabolic patients in Latin America revealed that women reported lower tobacco use during the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 36 Insomnia is one of the main factors associated with PAS use in this population group, 37 38 which has been a general increase in the consumption of prescription psychotropic drugs 39 as observed in the prevalence of psychotropic medication use identified in the study. A systematic review 39 demonstrated significant changes in PAS use among healthcare professionals during the COVID-19 pandemic that correlates with findings in the present study regarding the use of alcohol and other PAS. Alcohol was the most used substance with an increase of almost 14% in binge drinking, 1.3% in new alcohol users and a relationship between the alcohol use with the context generated by the pandemic, such as exposure to stressful environments, risk of contagion, neuropsychological conditions and high professional demands.…”
Section: Discussionmentioning
confidence: 73%
“…35 It showed that healthcare professionals who worked directly with COVID-19-infected/suspected clients were more likely to experience depression, stress and burn-out than those who were not personally involved in this fieldwork. 36 Insomnia is one of the main factors associated with PAS use in this population group, 37 38 which has been a general increase in the consumption of prescription psychotropic drugs 39 as observed in the prevalence of psychotropic medication use identified in the study. A systematic review 39 demonstrated significant changes in PAS use among healthcare professionals during the COVID-19 pandemic that correlates with findings in the present study regarding the use of alcohol and other PAS.…”
Section: Discussionmentioning
confidence: 80%
“…Bias assessment was conducted using the Cochrane risk of bias tool (Robvis 2.0), and the studies that did not contribute to the study objective (analyzing at least one variable) were considered to have a high risk of confusion and were reported. Robvis enables a comprehensive assessment of the overall confidence in the set of tests, taking into account factors such as the accuracy and relevance of the chosen studies as previously reported (22). Disagreements were resolved through consensus among the authors.…”
Section: Data Extraction Quality Assessment and Data Analysismentioning
confidence: 99%